2005
DOI: 10.1007/s10490-005-4117-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Networking with Colleagues Matter in Enhancing Job Performance?

Abstract: The present study empirically investigates the link between network properties and job performance using a sample of 121 middle managers from Beijing, China. The primary objective is to examine how characteristics of the person and the job moderate the effects of networks on self-rated performance. This study contributes to the network literature by investigating both the impact of network characteristics in terms of information accessibility and diversity on job performance and the interaction effects of gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Although it did not occur to us a priori, it is worth checking an interpretation of how this occurs. Chinese managers may actually have more kin in their professional networks (Chow & Ng, 2004;Ng & Chow, 2005;Peng, 2004), and thus the family-like patterns in our results may be driven by patterns of interaction with actual family members. Given this possibility, it is interesting to explore whether these results come from bringing kin into one's business, or from imposing family-like interaction norms on business associates who are not kin.…”
Section: Supplementary Analysesmentioning
confidence: 85%
“…Although it did not occur to us a priori, it is worth checking an interpretation of how this occurs. Chinese managers may actually have more kin in their professional networks (Chow & Ng, 2004;Ng & Chow, 2005;Peng, 2004), and thus the family-like patterns in our results may be driven by patterns of interaction with actual family members. Given this possibility, it is interesting to explore whether these results come from bringing kin into one's business, or from imposing family-like interaction norms on business associates who are not kin.…”
Section: Supplementary Analysesmentioning
confidence: 85%
“…By using the self-report and other ratings of EI scales, Law et al (2004a) have shown that EI is related to job outcomes in a mainland Chinese sample. Recent studies also show that the quality and nature of networking is one of the factors contributing to job performance and the success in careers of Chinese managers (Bu & Roy, 2005;Ng & Chow, 2005). Thus, it is reasonable to conclude that the relationship between EI and job outcomes should also be valid in mainland China.…”
Section: Purpose Of the Studiesmentioning
confidence: 98%
“…Second, we found mixed evidence for gender differences in relative status : One study found women’s successfully mobilized contacts were of a higher relative status than men’s (Whittington, 2018). Men and women’s network contacts appear to be of similar relative status in their expressive and general networks, yet no discernible pattern emerged for multiplex and instrumental networks (e.g., Markiewicz et al, 2000; Ng & Chow, 2005). Furthermore, only two studies examined relative status in relation to career outcomes, finding little support for UNC (Markiewicz et al, 2000; Ng & Chow, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Men and women’s network contacts appear to be of similar relative status in their expressive and general networks, yet no discernible pattern emerged for multiplex and instrumental networks (e.g., Markiewicz et al, 2000; Ng & Chow, 2005). Furthermore, only two studies examined relative status in relation to career outcomes, finding little support for UNC (Markiewicz et al, 2000; Ng & Chow, 2005). Only two studies (both in Chinese contexts) examined UNR, finding that general network contacts’ relative status was positively related to job performance (Ng & Chow, 2005) and income (Wang, Zhang, & Ni, 2015) for men and unrelated for women.…”
Section: Literature Reviewmentioning
confidence: 99%